Zika virus epidemiology in Bolivia: a seroprevalence study in volunteer blood donors - Saba Villarroel, Paola Mariela; Nurtop, Elif; Pastorino, Boris; Roca, Yelin; Drexler, Jan Felix; Gallian, Pierre; Jänisch, Thomas; Leparc-Goffart, Isabelle; Priet, Stéphane; Ninove, Laetitia; de Lamballerie, Xavier (PLoS neglected tropical diseases, 2018)
BACKGROUND: Zika virus (ZIKV), was widely reported in Latin America and has been associated with neuropathologies, as microcephaly, but only few seroprevalence studies have been published to date. Our objective was to determine the seroprevalence amongst Bolivian blood donors and estimate the future potential circulation of the virus. - METHODOLOGY: A ZIKV seroprevalence study was conducted between December 2016 and April 2017 in 814 asymptomatic Bolivian volunteer blood donors residing in various eco-environments corresponding to contrasting entomological activities. It was based on detection of IgG to ZIKV using NS1 ELISA screening, followed by a seroneutralisation test in case of positive or equivocal ELISA result. - CONCLUSIONS/SIGNIFICANCE: Analysis revealed that ZIKV circulation occurred in tropical areas (Beni: 39%; Santa Cruz de la Sierra: 21.5%) but not in highlands (~0% in Cochabamba, La Paz, Tarija). It was modulated by Aedes aegypti activity and the virus spread was not limited by previous immunity to dengue. Cases were geo-localised in a wide range of urban areas in Santa Cruz and Trinidad. No differences in seroprevalence related to gender or age-groups could be identified. It is concluded that ZIKV has been intensely circulating in the Beni region and has still a significant potential for propagating in the area of Santa Cruz.
Gesehen am 21.04.2020